Emotional Intelligence, Pain Knowledge, and Attitudes of Nursing Students in Hong Kong - Chan, J.; Hamamura, Takeshi (W.B. Saunders Co., 2014)
Research on nursing students' pain knowledge and attitudes is limited. Although emotions play a role in pain assessment, no study has examined the associations between emotional intelligence and pain knowledge and the attitudes of nursing students. This cross-sectional quantitative study aimed to address this research gap by assessing the pain knowledge and attitudes of nursing students in Hong Kong and examining associations between emotional intelligence and the pain knowledge and attitudes of nursing students. A total of 104 postgraduate nursing students (45 Year 1 students and 59 Year 3 students) completed a questionnaire that included demographic information, the Schutte Emotional Intelligence Scale (SEIS) and the Knowledge and Attitudes Survey Regarding Pain (KASRP). Data analyses included descriptive statistics, correlational analyses, chi-square test and t-tests. The pain knowledge and attitudes of both Year 1 students (M = 20.40, SD = 3.78) and Year 3 students (M = 21.36, SD = 3.15) were suboptimal, t(102) = –1.41, p = .16. Year 1 students had higher emotional intelligence (M = 122.44, SD = 8.90) than Year 3 students (M = 117.71, SD = 14.34), t(98.35) = 2.07, p = .04. For Year 1 students, emotional intelligence was negatively correlated with pain knowledge and attitudes, but the correlation was not significant (r = –.15, p = .33). For Year 3 students, emotional intelligence, pain knowledge and attitudes were negatively correlated, but the correlation was significant (r = –.31, p = .02). These results suggest that nursing students' pain knowledge and attitudes could be improved. Implications for nurse educators to enhance emotional intelligence and pain education for nursing students are discussed.